Patient engagement and patient support programs in allergy immunotherapy: a call to action for improving long-term adherence. Issue 1 (December 2016) - Demoly, Pascal; Passalacqua, Giovanni; Pfaar, Oliver; Sastre, Joaquin; Wahn, Ulrich
Abstract Allergy immunotherapy (AIT) is acknowledged to produce beneficial mid- and long-term clinical and immunologic effects and increased quality of life in patients with allergic respiratory diseases (such as allergic rhinoconjunctivitis and allergic asthma). However, poor adherence to AIT (due to intentional and/or non-intentional factors) is still a barrier to achieving these benefits. There is an urgent need for patient support programs (PSPs) that encompass communication, educational and motivational components. In the field of AIT, a PSP should be capable of (1) improving adherence, (2) boosting patient engagement, (3) explaining how AIT differs from pharmacological allergy treatments; (4) increasing health literacy about chronic, progressive, immunoglobulin-E-mediated immune diseases, (5) helping the patient to understand and manage local or systemic adverse events, and (6) providing and/or predicting local data on aeroallergen levels. We reviewed the literature in this field and have identified a number of practical issues to be addressed when implementing a PSP for AIT: the measurement of adherence, the choice of technologies, reminders, communication channels and content, the use of "push" messaging and social networks, interactivity, and the involvement of caregivers and patient leaders. A key issue is "hi-tech" (i.e. approaches based mainly on information technology) vs. "hi-touch" (based mainly on interaction with humans, i.e. family members, patient mentors and healthcare professionals). We conclude that multistakeholder PSPs (combining patient-, provider and society-based actions) must now be developed and tested with a view to increasing adherence, efficacy and safety in the field of AIT.